Effect of Forming Parameters on Profile Thinning of Flexible 3D Multi-Point Stretch Bending - Zhongyuan Shi; Yi Li; Jicai Liang; Ce Liang (Metals, 2021)
The ABAQUS finite element simulation software is used to simulate the flexible multi-point three-dimensional stretch bending process of aluminum profiles. The effect of process parameters on the web thickness of rectangular profile in flexible multi-point three-dimensional stretch bending is studied by orthogonal experiment and range analysis. The process parameters used in the experiments include pre-stretching value, post-stretching value, the number of multi-point dies and friction coefficient. The optimal combination of process parameters is obtained by numerical simulation and experimental verification. When the aluminum profile is completed flexible multi-point stretch bending according to the best parameters, the thickness thinning of outer web and inner web is the smallest. The experimental result is closed to the numerical simulated results. The effectiveness of the numerical simulation is verified by the corresponding experimental methods.